Modeling the impact of tuberculosis control measures in a highly endemic and an overcrowded prison / Herlianna Naning - Herlianna, Naning (2017)
Globally, the prevalence of tuberculosis (TB) is up to 100 times higher in closed settings such as prisons compared to the general population. Despite this, effecive TB interventions are rarely deployed in prisons in low and middle-income countries where the burden of TB is highest. Our aim was to explore the impact of introducing interventions to reduce the transmission of TB in an overcrowded prison in Malaysia. We used a deterministic transmission model to simulate the effects of three TB control strategies and evaluate their impact on the predicted prevalence of active TB over a tenyear period. In the first set of simulations, in which the current environmental situation (degree of cell crowding and ventilation rate) of the prison was held constant, we investigated the effects of isoniazid preventive therapy (IPT) and anti-tuberculosis treatment (ATBT), independently or as a combined strategy. We susbsequently repeated the simulations assuming improved environmental conditions. We also simulated the effect of prolonging IPT beyond the normal 6-months regimen, to 12 and 36 months. Our model showed that implementing either the ATBT or the combined IPT and ATBT strategy reduced the current 8% prevalence of active TB to below 2.5%, whereas implementing IPT alone increased the projected prevalance to 15%. After successful IPT treatment, reinfection compromises the effectiveness of IPT, irrespective of the treatment regime duration. Reducing overcrowding from six to four inmates per cell and increasing the ventilation rate from 2 to 12 air changes per hour improved IPT effectiveness by reducing the prevalence of active TB to 8% after ten years. To achieve control in such a high TB burden setting, there is an urgent need to implement effective TB interventions, like intensified TB case finding, IPT and environmental changes in the Malaysian prison.